Laowai as a discourse of Othering: unnoticed stereotyping of American expatriates in Mainland China - Liu, Yang; Self, Charles C. (Identities (Yverdon, Switzerland), 2020)
Homogeneous ethnic labels, deriving from migrants' phenotypic and cultural distinctness, are frequently utilised to single them out as the Other during intercultural encounters. Nonetheless, the Othering enacted by ethnic labelling has not attracted enough attention from host-nationals who use these labels. In-depth interviews with 35 American expatriates revealed that laowai was perceived as a discourse of Othering, which first categorised Westerners under this label as the Other in mainland China for their noticeable non-Chinese physical appearance, and then exposed them to its Chinese users' diversely motivated stereotyping in such forms as exclusion, alienation and discrimination. However, Chinese people had not noticed laowai's nature of being a stereotype-laden discourse of Othering and conversely considered this label as a neutral and even friendly expression. Ultimately, these Americans experienced Chinese people's habitual use of laowai as a way to separate them as permanent outsiders who were subject to Occidentalism in mainland China.